Effect of Extrusion Ratio on Microstructure and Properties of Al-1.5Fe-0.4Cr Alloy Obtained by Continuous Rheo-Extrusion - Yunhe Ning; Li Yang; Minqiang Gao; Renguo Guan (Metals)
Due to the shortage of primary Al resources and significant consumption of Al resources, recycled Al has become a focus of attention. In the process of recycling Al, the Fe element is the most hazardous impurity element, and the coarse Fe-containing phases lead to a reduction in the mechanical properties of recycled Al. In this work, an Al alloy with 1.5 wt% Fe and 0.4 wt% Cr was viewed as a recycled Al, approximately. The continuous rheo-extrusion technique was used to refine the Fe-containing phases in the Al-1.5Fe-0.4Cr alloy, improving the mechanical properties of the alloy. The effect of the extrusion ratio on the microstructure and properties of the continuous rheo-extrusion was investigated. The results showed that, when the extrusion ratio was changed from 4 to 5, the percentage of low-angle grain boundaries in the alloy increased from 45.5% to 53.1%, the average orientation angle reduced from 23.9° to 23.3°, and the grain size decreased from 4.3 ± 0.2 μm to 2.6 ± 0.1 μm. As a result, the ultimate tensile strength, yield strength and elongation of the alloy, with an extrusion ratio of 5, were 161.5 ± 2.8 MPa, 112.3 MPa ± 2.6, and 36.9% ± 1.6%, respectively. Grain refinement and Fe-containing phase refinement were responsible for the improvement in the mechanical properties of the alloy.